Pengaruh Pendidikan Dan Pengangguran Terhadap Kemiskinan Di Kota Probolinggo, Kabupaten Probolinggo, Kabupaten Lumajang - Imas Cik Hanun; prayudi setiawan prabowo (Universitas Negeri Surabaya, 2022)
The purpose this research is to find out how influential education and unemployment are on proverty in Probolinggo Regency, Probolinggo City and Lumajang Regency, using a quantitative associative approach with a research period of 11 (eleven) years, form 2010 to 2020. The data used are secondary data using a panel analysis tool, composed of cross-sectional data form 3 Regencies/Cities in East Java and time series data for the periode 2010-2020. The results show that proverty in probolinggo City, Probolinggo Regency and lumajang Regency can be explained by education and unemployment of 82%. Education and unemployment simultaneously have an influence on proverty with a probability value of 0.000000. Partially education with indicators of high school graduates > 15 years has no effect on proverty, has a probability of 0.4811, while unemployment with an indicator of poor people not working > 15 years has an influence on proverty, the probability is 0.0017.